PENGETAHUAN DAN DUKUNGAN SUAMI TENTANG PEMBERIAN ASI EKSKLUSIF DI KELURAHAN CAMBAYA KOTA MAKASSAR - Afriani, Afriani; Wirawati Amin,; Fitriati Sabur,; Hariyanti, Hariyanti (Jurnal Cakrawala Ilmiah, 2023)
Relationship between Knowledge and Support of Husband with the Exclusive Giving of Breast milk in Cambaya Village, Makassar City, (guided by Hj. Hidayati and Afriani) Exclusive breast milk is breast Milk which is given to babies as the main food that can be well received by the baby's digestive system and given exclusively for 6 months. Knowledge of the importance of exclusive breastfeeding is needed by mothers and families because breast milk is the first and main intake for the babys health at this time. In addition to the support of husband and family also has its own factors in influencing the psychological condition of the mother which will have an impact on the success of breastfeeding. More over support of husband and family also has own factors in influencing the psychological condition of mother who will have an impact to the success of breastfeeding. This study aims to determine the relationship between husband's knowledge and support with exclusive breastfeeding, with analytical survey methods and with a cross sectional approach. Subjects of this study were 78 mothers who had infants aged 6-12 months whose was determined by using the Sanley Lemeshow formula and include to the criteria. The research design uses purposive sampling technique. The statistical analysis used in this study was the chi-square statistic, with a confidence level of α = 0.05. The results of the research obtained from sufficient maternal knowledge can motivate exclusive breastfeeding in the cambaya village, husband's support which is sufficient can motivate the mother to give exclusive breastfeeding in the cambaya village. So that it can be concluded that there is a relationship between knowledge and support of husbands with exclusive breastfeeding in Cambaya Makassar. Therefore, it is expected that there is a need to increase the role of health workers in providing information and information about the importance of exclusive breastfeeding. Beside that, husband and family support is also needed to provide support and encouragement so that mothers can breastfeed well.